COMMUNITY STRUCTURE OF MACROZOOBENTHOS IN THE MELIBUR RIVER, MAYANG SARI VILLAGE MERBAU DISTRICT, KEPULAUAN MERANTI REGENCY RIAU PROVINCE - Safruddin '; Adriman '; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractMacrozoobenthos that live in the base of a river is commonly used asbioindicator as its presence is depended on the water quality of the river ingeneral. To understand the community structure of the macrozoobenthos in theMelibur River, a study has been conducted on 7 - 22 January 2015. Samples weretaken from 3 stasions, close to sago industry outlet (S), around the river mouth2(S2) and in the area close to harbor (S3). There were 3 plots in each station.Sampling was conducted 3 times, once/ week. Parameters measured were theabundance, uniformity and dominancy index of the macrozoobenthos and severalwater quality parameters such as temperature, current speed, turbidity, depth,salinity, dissolved oxygen, pH, substrat type, and organic materials.Results shown that there were 11 species (4 classes) of macrozoobenthos,2094 organisms /m2. There were Gastropods (42,45%), Polychaeta (25,03%),insects (7,50%), Oligochaeta and Bivalvas are (5,01%). The highest density ofmacrozoobenthos was in the S3 (1151 organisms/m2) and the lowest was in theS1 (419 organisms /m2). The H’ was 2,9749 and 1.5616 in S3 and S1respectively and uniformity index (E) was 0.99 in S1 0,79 S2, and 0.94 in S3.The C value was 0.34 in S1 and 0.14 in S3. There was muddy sand substratein S1 and S2 and sandy substrat in S3 with 19.16% – 37.5% organic materialcontent in each area. Data obtained that the type of substrate strongly affect thetype of macrozoobenthos present.Key word: Community, Makrozoobenthos, Melibur River, Kepulauan MerantiRegency